Improving Coordination During Care Transition between Ambulatory and Inpatient Care Facilities: Evaluating the Utilization and Scope of Ehr Facilitated Longitudinal Plan of Care (International Journal of Nursing Education, 2021)
Gaps in generation and timely transfer of relevant information during care transitions remain a greatchallenge to care coordination. Electronic Health Record (EHR) based information transfer tools are notefficiently used by most providers. The objective of this project was to understand the current process of caretransition between ambulatory and inpatient care setting and to explore the utilization and scope of an EHRbased Longitudinal Plan of Care in improving coordination during care transition. The Longitudinal Planof Care when compared with transition of care practices recommended by Transitions of Care ConsensusConference and National Transitions of Care Coalition work group showed that it lacked some informationpertinent to care coordination. The survey performed indicated that most commonly used Electronic HealthRecord tool for care transition were notes and chart reviews (97.4%, 93.4%). Only 12% of the participantsexpressed high satisfaction with the currently used tool. Among the participants who used the LongitudinalPlan of Care, only 8.8% reported it as a sufficient tool for information transfer. Majority (93.5%) wereunaware that such a tool existed and had never explored its functionality. Improving the functionality ofLongitudinal Plan of Care and training health care providers can greatly facilitate information transferduring care transition.
Keywords: Care transition; Electronic Health Record; Longitudinal Plan of Care; Care coordination; Inpatient care setting; Ambulatory care setting